RANCANGAN Rancangan Sistem Pendaftaran Online Pasien Rawat Jalan Berbasis Web dengan PHP Sistim Pendaftaran Online - Miftachul Ulum (JOURNAL OF MEDICAL RECORDS AND HEALTH INFORMATION, 2020)
The registration system is a process that is carried out before the patient gets service in the treatment room. Hasta Husada Special Surgery Hospital uses a manual registration system. The purpose of this study was to design an online web-based outpatient registration system at the Hasta Husada Kepanjen Special Surgery Hospital. The research method used is SLDC Waterfall. The final product trial questionnaire was analyzed using PIECES analysis (Performance, Information, Economy, Control, Efficiency, Service). The study population consisted of 8 registration officers and 1 IT officer, and the study sample consisted of 1 registration officer and 1 IT officer. Based on the results of the PIECES analysis on the use of a manual registration system, Performance, Information, Economy, Control, Efficiency, Service analysis gets a total value of 0 each from a total of 1 respondent.While on the use of an online registration system, Performance, Information, Economy, Control, Efficiency, Service analysis gets a total of 2 each from a total of 1 respondent. It can be concluded that the use of an online registration system is more effective than using a manual registration system. So it is recommended that hospitals can use the online registration system application to simplify the patient registration system in outpatient registration services. Keywords: Design, Registration System, Online, Patient, Outpatient